Rocío Badía Fumaz & Eva Ariza Trinidad (Eds.) (2025). «Strange Places of Fiction». Madrid: Guillermo Escolar Editores. 304 pages (Castilla. Estudios de Literatura, 2026)
The distinction between fiction and non-fiction remains one of the most widely discussed issues in literary theory. The volume Strange Places of Fiction, coordinated by Rocío Badía Fumaz and Eva Ariza Trinidad, from the Department of Theory of Literature and Comparative Literature at the Complutense University of Madrid, challenges this opposition. Adopting a predominantly pragmatic approach, it analyzes how texts traditionally considered factual incorporate fiction in more or less punctual ways and with functions that expand their communicative, aesthetic, and creative potential. Through the nine studies included in this volume —focused on explicit poetics, the initiatory poem, narratives of spiritual illumination, science fiction, “true crime,” and epistolary writing— the book offers a theoretically grounded reflection that proposes rethinking the relationship between fiction, factuality, and contemporary discursive practices.
Keywords: Fictionality; Factual literature; Pragmatic approach